Does biochar application enhance soil salinization risk in black soil of northeast China (a laboratory incubation experiment)?. Issue 11 (19th September 2021) - Meng, Qingfeng; Zhao, Shuo; Geng, Ruihong; Zhao, Ying; Wang, Yong; Yu, Fei; Zhang, Juan; Ma, Xianfa
ABSTRACT: Generally, application of biochar is an important management practice that can affect soil physico-chemical and biological properties. However, biochar is characterized by high pH and ash content, and due to this, little is known of potential salinization risk of application of biochar to soil. Laboratory incubation experiments were conducted with three replications comprising five treatments according to application rates of biochar (0, 50, 100, 200 and 400 g kg −1 (wt/wt)). The results indicated that application of corn straw biochar to black soil at the rate of 400 g kg −1 resulted in significant increases in soil pH, electrical conductivity (EC) and exchangeable K + and soluble K +, Ca 2+ and Mg 2+, and decreases in cation exchange capacity (CEC) and exchangeable Ca 2+ in comparison to untreated soil. Based on stepwise regression analysis, the dominant independent variable that affected soil pH was exchangeable K + saturation percentage. In addition, EC was significantly positively related to potassium adsorption ratio (PAR). It was concluded that increased soil pH and EC are related to biochar (pyrolysis temperature of 600 °C) with higher concentration of K + and lower CEC. This is due to increased exchangeable and soluble K + and decreased soil buffering capacity from high application rate of biochar.